Introduction: Approaches to Childbirth in the Middle Ages. - Cormack, Margaret (Journal of the History of Sexuality, 2012)
An introduction is presented to articles within the issue on the subject of childbirth during the Middle Ages on topics which include medieval culture, infanticide and the legal systems in medieval western Europe.